Crohn's disease and nursing care from a patient treated with corticosteroids: a case report - Shima Heidary; Haydeh Heidari (Nursing and Health Sciences Journal (NHSJ), 2022)
Crohn's is an inflammatory bowel disease that is treated with corticosteroids and has many side effects that nurses should be aware of during treatment. An 11-year-old girl was hospitalized with heartburn and dysentery with a diagnosis of Crohn's disease. Interventions performed for the patient included vital signs control every 6 hours. The itching was one of the symptoms during corticosteroid injection, which gradually decreased in severity. The nursing team did not provide any effective intervention for the patient's corticosteroid therapy. Patients undergoing corticosteroid therapy with interventions such as Control of vital signs from the first day of corticosteroid treatment, six hours before, during, and after administration, at different times, up to 24 hours Full. Measurements of blood glucose, serum sodium and potassium, and electrocardiogram should be performed before and four hours after administration on each day of corticosteroid therapy, as well as a corticosteroid injection time of more than 45 minutes.